2018
DOI: 10.3390/photonics5040038
|View full text |Cite
|
Sign up to set email alerts
|

High-Power Passive Fiber Components for All-Fiber Lasers and Amplifiers Application—Design and Fabrication

Abstract: The most important components for application in high-power all-fiber lasers and amplifiers are, most of all, power combiners, but also mode field adaptors. This paper summarizes recent achievements in the area of development and fabrication of high-power passive fiber components. The principles of operation and basic design and fabrication criteria, which have to be taken into account while designing the aforementioned components, are explained in detail. The most recent impressive achievements are summarized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 83 publications
(127 reference statements)
0
10
0
Order By: Relevance
“…The SPC with four pump input fibers at a coupling efficiency of 90%, low loss, and excellent signal feed-through properties has comparable performance characteristics to components based on standard step-index fibers for signal feed-through (c.f. reference 13 ). This was enabled by altering the cladding shape of the CCC-fiber along a section of 20 mm (required for SPC manufacturing) with the presented CO 2 -laser ablation process.…”
Section: Discussionmentioning
confidence: 99%
“…The SPC with four pump input fibers at a coupling efficiency of 90%, low loss, and excellent signal feed-through properties has comparable performance characteristics to components based on standard step-index fibers for signal feed-through (c.f. reference 13 ). This was enabled by altering the cladding shape of the CCC-fiber along a section of 20 mm (required for SPC manufacturing) with the presented CO 2 -laser ablation process.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the technical scope and fabrication complexity of SPCs are relatively larger than PCs; hence the brief overview of power scaling advances in this section mainly focuses on SPCs. Most of the fabrication processes or technical details are similar for both the SPCs and PCs, and more details on the fabrication techniques or research progress can be found in other review articles [152,153].…”
Section: High-power Fiber Combinermentioning
confidence: 99%
“…The key components in the DCF link are cladding power strippers (CPSs), a tapered fiber bundle combiner (TFBC), and a tapered fiber bundle divider (TFBD). In these components, TFBCs are commonly utilized for high-power fiber lasers and amplifiers with DCFs [58], [59]. Fig.…”
Section: A Experimental Setupmentioning
confidence: 99%